KONTRIBUSI KEPEMIMPINAN KEPALA SEKOLAH: Profesionalisasi Guru dan Iklim Sekolah terhadap Motivasi Kerja Guru di MTsN Pasir Lawas Kabupaten Tanah Datar - Erwin Erwin (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Contribution Leadership of Head Scholl: Professionalization of Teachers and School Climate to Teacher Work Motivation in MTsN Pasir Lawas Tanah Datar. Based on observations in the field, was impressed that the junior secondary school teachers' motivation Affairs (MTsN) Pasir Lawas Tanah Datar low, it is influenced by the leadership of the principal, teacher professionalization and school climate. If the condition is left is feared will affect efforts to improve the quality of education State in junior secondary school (MTsN) Pasir Lawas Tanah Datar. This study aims to reveal how much the contribution of principal leadership, teacher professionalization and school climate Against junior secondary school teachers' job motivation Affairs (MTsN) Pasir Lawas Tanah Datar. The hypothesis tested in this study were: (1) the principal's leadership contributed Against motivation of teachers (2) Against the Professionalization of teachers' motivation to contribute to the work of teachers (3) school climate contribute Against motivation of teachers (4) principal leadership, teacher professionalization, and school climate contribute Against teacher motivation.Kata Kunci: Kepemimpinan, profesionalisasi, motivasi kerja